Decanoato de nandrolona altera a função do ventrículo esquerdo por aumentar a relação SERCA-2a/fosfolambam em ratos SHR: efeitos prevenidos pelo enalapril - Melo Junior, Antonio Ferreira de (2017)
Abuse of steroids is a matter of concern especially the effects of anabolic androgenic steroids (AAS) on cardiovascular function. Data demonstrate the occurrence of arterial hypertension, cardiomyopathies, arrhythmias, heart failure and sudden cardiac death, depending on the duration of use. Hypertension already affects about 27% of the Brazilian population and many of these people do not even know. In recent years much has been studied about the losses of AAS in experimental models, however, these studies are limited to normotensive animals. Thus, the objective of this work was to evaluate the parameters of contractility and proteins involved in the intracellular calcium dynamics after a 4- week Nandrolone Decanoate (DN) treatment, associated with Enalapril. The subjects were 12 week-old SHR males divided into 4 groups. The group of hypertensive rats was divided into the following experimental groups treated with: vehicle (Control), Enalapril 10mg/ kg/day (ENALAPRIL), Nandrolone Decanoate 10mg / kg (DN) and Enalapril + Nandrolone Decanoate (DN+E). Systolic blood pressure (PAS) was indirectly assessed by the tail plethysmography method. After receiving anesthesia via peritoneal ketamine (30mg / kg,) and xylazine (3mg / kg), the animals were submitted to catheterization of the right carotid artery to evaluate cardiac function. The data were presented by means of the Left Ventricular Systolic Pressure (LVSP), of the temporal derivatives (dP/dtmax mmHg/sec), positive and negative, and TAU. The heart was collected for histological analysis (H&E) and deposition of collagen (picrosirius red). Analysis of the proteins expression related to cytosolic Ca2 + handling was performed by the Western blot method. Treatment with DN does not alter the final body weight, however it reduces epididymal fat and enalapril is able to prevent this change when associated with DN. In addition, DN increased the ratio of prostate weight to tibial length and enalapril is not able to prevent this increase. The animals presented similar initial SBP, however, after the end of the treatment enalapril reduced SBP, the DN increased this parameter and in the Decanoate + enalapril group the increase was reversed. The DECA increases the LVSP and the positive and negative derivatives in relation to the control, the enalapril alone does not alter this parameter and the association is able to reverse this alteration. TAU is reduced in the DN group and the association with enalapril partially reverses this parameter. SERCA-2a and p-PLB-Ser16 proteins as well as the SERCA-2a / PLB ratio are increased in DN animals and enalapril is able to prevent this increase. Thus, we conclude that Nadrolone Decanoate alters cardiac function and enalapril is able to revert the changes observed in SHR animals.